Solution and Stability of Quartic Functional Equations in Modular Spaces by Using Fatou Property - N. Uthirasamy; K. Tamilvanan; Hemant Kumar Nashine; Reny George (Journal of Function Spaces)
We propose a novel generalized quartic functional equation and investigate its Hyers–Ulam stability in modular spaces using a fixed point technique and the Fatou property in this paper.